2012
DOI: 10.1590/s1983-14472012000300025
|View full text |Cite
|
Sign up to set email alerts
|

Revisão integrativa: um retrato da morte e suas implicações no ensino acadêmico

Abstract: GDO, et al. Revisão integrativa: um retrato da morte e suas implicações no ensino acadêmico. Rev Gaúcha Enferm. 2012;33(3):190-197

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
24

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 13 publications
0
7
0
24
Order By: Relevance
“…The training courses attach little importance to the approach on terminality, becoming a matter of concern since the health professional's encounter with death becomes inevitable in the work environment. 7 Another study 8 points out that, coupled with the professional's unpreparedness in developing this kind of care, there may be internal difficulties that limit the ability to express feelings about terminal patients and also to listen to them. Such difficulties are understood as a defensive attitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The training courses attach little importance to the approach on terminality, becoming a matter of concern since the health professional's encounter with death becomes inevitable in the work environment. 7 Another study 8 points out that, coupled with the professional's unpreparedness in developing this kind of care, there may be internal difficulties that limit the ability to express feelings about terminal patients and also to listen to them. Such difficulties are understood as a defensive attitude.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that address the process of death and dying, 5 some indicate the perspective of the nurse 7,9 and others of the caregiver. 3,10 However, besides the author Kübler-Ross, 5 No further study was found that accompanies the patient in this process.…”
Section: Introductionmentioning
confidence: 99%
“…O tema é tratado como tabu e negado, mas em flagrante contradição, a cada dia ele se impõe no imaginário coletivo, à medida que é divulgado indiscriminadamente por veículos de comunicação de forma espetaculosa (1) . Essa contradição se reflete nos currículos de formação dos profissionais de saúde, que apesar de conviverem cotidianamente com a morte por força do ofício, raramente tem a oportunidades de refletir sobre a perda dos pacientes e sobre o impacto da morte de cada um deles em sua vida pessoal e profissional (2) . Como consequência os alunos não são estimulados a identificar seus sentimentos e reações emocionais, bem como, os dos pacientes e familiares frente ao processo de adoecimento e morte.…”
Section: Introductionunclassified
“…Como consequência os alunos não são estimulados a identificar seus sentimentos e reações emocionais, bem como, os dos pacientes e familiares frente ao processo de adoecimento e morte. Dessa forma, formam-se profissionais com dificuldades de prestação de cuidados integrais, éticos e humanizados àqueles que estão vivenciando o final da vida (2)(3)(4) . Em geral, na terminalidade a opção pela hospitalização, retira o doente de seu ambiente familiar favorecendo a perda de sua autonomia e a exclusão no processo decisório sobre a sua própria vida (5) .…”
Section: Introductionunclassified
“…Não ocorrendo possibilidade de cura, é preciso lidar com as doenças até o final da vida do paciente visto que, na aproximação da morte, revelam-se atitudes e reações emocionais, que não resultam apenas de um aprendizado cultural (4). Em síntese, embora essa realidade não possa ser alterada, podemos exercer um efeito significativo sobre a maneira pela qual os pacientes evoluem nesse processo, sobre como este ocorre e sobre as suas memórias resultantes para as famílias (5).…”
Section: Introductionunclassified